(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
Introduction: It is considered now-a-days that patients with transverse craniofacial deformity might have differences in masticatory muscle activity between both sides; and as masticatory muscle activity takes place throughout the usual daily life; therefore, it might have some relation with the transverse craniofacial morphology. The present study was carried out to find out any association between balance of masticatory muscle activity during usual daily life and transverse craniofacial morphology or tooth contact area in patients with transverse jaw deformity. Subjects and Methods: All the controls and patients for the study were selected from our staffs and patients coming to Orthodontic Clinic, Hiroshima University Dental Hospital, respectively. Thirteen males and two females (mean and s.d. of ages: 28.6 ± 1.9 years) served as the controls. They had Angles Class I molar relationship, no severe malocclusion, no complaints of temporomandibular disorder (TMD).The patient group was consisted of 10 males and five females (mean and s.d. of ages: 19.9 ± 5.3 years) with lateral shift of the mandible. They had malocclusion such as cross-bite and severe crowding, but no complaints of TMD. Portable digital EMG recording device were used to record the EMG from the bilateral masster and anterior temporal muscles. The diurnal recording was carried out for consecutive 142 minutes and divided into two periods of usual daytime and mealtime for analysis. After the diurnal recording, the subjects were allowed to go back home with the electrodes in position and then nocturnal EMG recording was performed again at night with the usual sleeping posture for 142 minutes. Posteroanterior cephalometric analysis and tooth contact area were measured for all the subjects. Result: No significant correlations were found for both the muscles neither with transverse craniofacial morphology nor with the tooth contact area for all the three periods of usual daily life, although a significant correlation was detected between the A-B distance and AI of the anterior temporal muscle during usual daytime. Conclusion: It is suggested that masticatory muscle activity during usual daily life in patients with transverse craniofacial deformity may not be related only to such factors as skeletal deformity or tooth contact area but governed by other important factors like occlusal interference, premature contacts, instability and so on. Ban J Orthod & Dentofac Orthop, October 2012; Vol-3, No.1